13 Association of arterial stiffness to left ventricular remodelling in heart failure with preserved ejection fraction. (March 2019) - Athithan, Lavanya; Kanagala, P; Singh, A; Gulsin, GS; Graham-Brown, MPM; McAdam, J; Marsh, A; Parke, K; Wormleighton, J; Arnold, JR; Squire, IB; Ng, LL; et al.
Abstract : Background: Arterial stiffness has been implicated in the pathophysiology of Heart Failure with Preserved Ejection Fraction (HFpEF) and has been postulated to be related to adverse left ventricular (LV) remodelling. Purpose: To determine whether arterial stiffness measured by cfPWV (Oscillometry) and Aortic distensibility (AoD) are independently related to LV remodeling in HFpEF. Methods: We prospectively recruited 140 patients with HFpEF who underwent VICORDER® assessment of cfPWV and a multiparametric cardiac MRI which included a cine, perpendicular to the thoracic aorta at the pulmonary artery bifurcation with simultaneous blood pressure recording. Images were analysed using Circle CVi and aortic images were analysed in Java Image Manipulation. Aortic (Ao) distensibility was calculated using the formula Distensibility = (Ao max – Ao min)/(Ao min × pulse pressure). Results: 134 (65 males) of the patients had either cfPWV or distensibility measured using MRI, with an average age of 73±9.4 years, mean BP 144.7±24.9/74.0±13.9 mmHg. 73 patients (54.4%) with a diagnosis of diabetes, 121 patients (90.2%) with known hypertension, average BMI of 33.7±7.0. Mean cfPWV was 9.57±2.42 and aortic distensibility was 1.13±0.70 in the ascending and 1.28±1.02 in the descending aorta. Average measures for LV remodelling and function were: LV Mass Index 52.35±14.83 g/m 2 ; LV Mass/Volume 0.96±0.19 and ejection fraction 56.11%±5.48%. Aortic stiffness (data for ascending aortic distensibility and cfPWV shown respectively) was not significantly related to any measure of LV remodelling: LV Mass r=0.023, p=0.824 and r=0.036, p=0.703; LV Mass Index r=−0.063, p=0.531 and r=0.110, p=0.243; LV Mass/Volume r=0.111, p=0.272 and r=0.068, p=0.467. Factors that showed a significant effect in the univariate analysis were gender, presence of diabetes, level of HbA1c and average heart rate, but in the multivariate analysis, only gender remained significant. Conclusion: In patients with established HFpEF, aortic stiffness measured by CMR or oscillometry, is not associated with adverse LV remodelling. Whether aortic stiffness is related to pre-symptomatic LV remodelling warrants further study. Funding acknowledgement: This research was funded by the NIHR Leicester Cardiovascular Biomedical Research Centre